A digital transfer film coating and its preparation method and application
By providing a digital transfer film coating with a specific ratio, the existing digital printing film has been solved, and the problem of frequent coating times, low efficiency and high cost is achieved that it is possible to form suitable for digital printing on the substrate with only one process. The coating ensures stable peeling of the image from the substrate.
Patent Information
- Application Number
- CN202310894723.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The existing digital printing films require the application of multiple coatings on the substrate in sequence, with many coating times, low efficiency, high cost, and difficult to meet the two major needs of ink absorption and release.
A digital transfer film coating is provided, which consists of wax, thickener, adhesive, color fixing agent, leveling agent, disintegrant and filler, and forms a single layer coating suitable for digital printing through a specific combination. The layer can easily peel off the image and the substrate by hot-staining tear after hot-staining.
It is realized that the coating suitable for digital printing can be formed on the substrate in only one process, which improves the coating efficiency and cost-effectiveness, and ensures stable peeling of the image and the substrate.
Smart Images

Figure GDA0004736908870000051 
Figure GDA0004736908870000061 
Figure GDA0004736908870000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of digital inkjet printing coatings, and in particular to a digital transfer film coating and a preparation method and application thereof. Background Art
[0002] In recent years, digital printing technology has received widespread attention at home and abroad. Digital printing is not limited to the shape of the product, and has the characteristics of simple operation and exquisite printed products. Among them, digital printing film is one of the core technologies of digital printing.
[0003] At present, commonly used digital printing films need to be coated with multiple coatings on the substrate to form multiple coatings, such as release layers and ink-fixing layers. For example, the invention patent with publication number CN106808820A discloses a transfer film prepared by digital printing, which has a water-based wax layer and a color graphic layer in addition to the substrate; the digital transfer film disclosed in the invention patent with publication number CN113022185A includes two coating layers, a water-based interface peeling layer and a water-based ink-bearing layer; the water-based jet transfer material disclosed in the invention patent with publication number CN109334292A includes a substrate layer, a release layer and an ink layer in sequence; these existing digital printing films all need to be coated with multiple coatings on the substrate in sequence, with many coating times, low efficiency and high cost.
[0004] Therefore, in order to improve production efficiency, it is very necessary to develop a digital transfer film coating that can meet the two major requirements of ink absorption and release. The developed digital transfer film coating can be printed and can be completely peeled off from the surface of the substrate. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a digital transfer film coating and a preparation method and application thereof. The digital transfer film coating provided by the present invention is suitable for preparing digital transfer film, has good coating effect on the substrate, is non-sticky, non-cracking, and non-powder-adhering. The coating formed by the coating can easily peel off the image and the substrate by hot or cold tearing after hot stamping, and can meet the needs of digital printing.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a digital transfer film coating, comprising the following components in parts by weight: 30 to 70 parts of wax, 1 to 3 parts of thickener, 3 to 30 parts of adhesive, 10 to 25 parts of color fixing agent, 1 to 8 parts of leveling agent, 0.1 to 2 parts of disintegrant and 5 to 30 parts of filler.
[0008] The digital transfer film coating provided by the invention is suitable for preparing a digital transfer film, has a good coating effect on a substrate, is non-sticky, non-cracking, and non-powder-adhering.
[0009] Compared with the prior art, the digital transfer film coating provided by the present invention only requires one process to form a coating layer after coating, with a small number of coating layers, high coating efficiency and relatively low cost; after hot stamping, the formed coating can easily peel off the image and the substrate by hot or cold tearing, meeting the needs of digital printing.
[0010] The present invention uses wax as the main component, does not require a catalyst for catalytic reaction, and requires a short thermal curing time; the present invention can inhibit the migration of wax to the coating surface by optimizing the wax, adhesive and filler, thereby improving the strength, smoothness and peeling stability of the coating.
[0011] As a preferred embodiment of the present invention, the digital transfer film coating includes the following components in parts by weight: 40 to 50 parts of wax, 1 to 2 parts of thickener, 15 to 24 parts of adhesive, 12 to 18 parts of color fixing agent, 1.5 to 2.5 parts of leveling agent, 0.5 to 1 part of disintegrant and 15 to 20 parts of filler.
[0012] As a preferred embodiment of the present invention, the melting point of the wax is 58 to 130°C, more preferably 80 to 120°C.
[0013] As a preferred embodiment of the present invention, the wax includes a first wax and a second wax, the melt viscosity of the first wax after drying is not higher than 80 mpa·s, and the melt viscosity of the second wax after drying is greater than 80 mpa·s.
[0014] Furthermore, the weight ratio of the first wax to the second wax is (0.2-5):1, more preferably (0.5-2):1.
[0015] Furthermore, the first wax includes at least one of montan wax emulsion, Fischer-Tropsch wax emulsion, and aqueous erucamide emulsion; the second wax includes at least one of polyethylene wax, silicone wax, paraffin wax, microcrystalline wax, and palm wax.
[0016] Research has found that by combining two waxes with different melt viscosities in a specific ratio, the prepared digital transfer film coating has a good coating effect on the substrate, the hardness of the formed coating is high, the strength and smoothness of the coating can be improved, and the coating is easy to transfer and peel off.
[0017] As a preferred embodiment of the present invention, the filler has a particle size D90 of no more than 15 μm and an oil absorption value of no less than 30%. Studies have shown that fillers with an oil absorption value of no less than 30% have good hydrophilicity and can also improve the surface smoothness of the coating formed by the digital transfer coating.
[0018] As a preferred embodiment of the present invention, the filler includes a first filler and a second filler; the first filler and the second filler are fillers of the same type but with different particle sizes or fillers of different types but with different particle sizes, and the weight ratio of the first filler to the second filler is (0.2-5):1, and more preferably (1-2):1.
[0019] Furthermore, the first filler is selected from at least one of acrylic copolymers, silica, calcium carbonate, kaolin, fumed alumina, zinc stearate, calcium stearate, talc, and titanium dioxide, and the particle size D90 of the first filler is less than 5 μm; the second filler is selected from at least one of acrylic copolymers, silica, calcium carbonate, kaolin, fumed alumina, zinc stearate, calcium stearate, talc, and titanium dioxide, and the particle size D90 of the second filler is 5 to 15 μm.
[0020] Research has found that by combining fillers of different particle sizes in a specific ratio, the coating formed by the digital transfer coating has a uniformly distributed microporous structure, which can effectively provide the coating with ink absorption, release and smoothness.
[0021] As a preferred embodiment of the present invention, the disintegrant is selected from at least one of dry starch, sodium carboxymethyl starch, hydroxypropyl methylcellulose and cross-linked polyvinylpyrrolidone.
[0022] As a preferred embodiment of the present invention, the digital transfer film coating further comprises water, and the weight proportion of the water in the digital transfer film coating is 80 to 120 parts.
[0023] In a second aspect, the present invention provides a method for preparing the digital transfer film coating as described in the first aspect, comprising the following steps:
[0024] The digital transfer film coating is obtained by mixing water, wax, thickener, adhesive, color fixing agent, leveling agent, disintegrant and filler.
[0025] In a third aspect, the present invention provides a use of the digital transfer film coating as described in the first aspect in preparing a digital transfer film.
[0026] As a preferred embodiment of the present invention, the method for preparing the digital transfer film comprises the following steps: coating the digital transfer film coating on a substrate, and drying to obtain the digital transfer film.
[0027] Furthermore, the thickness of the substrate is 35-100 μm.
[0028] Furthermore, the coating amount of the digital transfer film coating is 2 to 6 g / m 2 , the coating temperature is 70-140°C.
[0029] It has been found that if the coating temperature is controlled during coating to be lower than the melting point of the wax in the digital transfer film coating, the migration of the wax to the coating surface can be inhibited, thereby improving the strength, smoothness and peeling stability of the coating.
[0030] Furthermore, the coating method includes any one of slit coating, slide coating, knife coating, anilox roller coating and doctor bar coating.
[0031] Furthermore, the drying temperature is 70-140°C.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The digital transfer film coating provided by the present invention only requires one process to form a coating layer after coating, with a small number of coating layers, high efficiency and relatively low cost;
[0034] (2) After hot stamping, the coating formed by the digital transfer film coating of the present invention can easily peel off the image from the substrate by hot or cold tearing, thus meeting the requirements of digital printing.
[0035] (3) The present invention uses wax as the main component, does not require a catalyst to catalyze the reaction, and requires a short thermal curing time. The present invention can inhibit the migration of wax to the coating surface by optimizing the wax, adhesive and filler, thereby improving the strength, smoothness and peeling stability of the coating. DETAILED DESCRIPTION
[0036] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0037] Unless otherwise specified, the reagents, methods and equipment used in the present invention are all conventional reagents, methods and equipment in the art.
[0038] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the sources of the components used in the following embodiments and comparative examples are listed below:
[0039] Adhesive: Styrene-butadiene latex, Trinseo, model: Ligos 3693;
[0040] Thickener: guar gum, guar gum;
[0041] Fixing agent: calcium chloride, Ledacon 3524;
[0042] Leveling agent: polyether modified siloxane, model BYK333;
[0043] Polyethylene wax: melting point is 120℃, melt viscosity after drying is 110mpa·s, Longhai Chemical, model is LHWAX TM 202;
[0044] Montan wax emulsion: melting point is 82℃, melt viscosity after drying is 60mpa·s, Longhai Chemical, model is LHWAX TM 5017 anodized aluminum release agent;
[0045] Fischer-Tropsch wax emulsion: melting point is 105°C, melt viscosity after drying is 100 mPa·s, Jiechuang, model W-143;
[0046] Aqueous erucamide emulsion: melting point 85°C, melt viscosity after drying 40mpa·s, Zhongda, model WYS-30;
[0047] Silica: particle size D90≤1μm, oil absorption value 300%, Wanhua Tianhe, product name is hydrophilic white carbon black;
[0048] Talc: particle size D90≤9μm, oil absorption value 30%, boulder, model 1250;
[0049] Acrylate copolymer: particle size D90≤4μm, oil absorption value 80%, Japan Sumitomo PMMA;
[0050] Calcium stearate: particle size D90≤2μm, oil absorption value 60%, Wangjiang brand calcium stearate;
[0051] Kaolin: particle size D90≤9μm, oil absorption value 60%, boulder js-glt;
[0052] Calcium carbonate: particle size D90≤11μm, oil absorption value 50%, Zhejiang Changhongyi 2000;
[0053] Fused alumina: particle size D90≤9μm, oil absorption value 50%, Haiyu 53.
[0054] The melt viscosity of the above-mentioned polyethylene wax, montan wax emulsion, Fischer-Tropsch wax emulsion and aqueous erucamide emulsion is tested using a melt viscometer. The specific steps of the test are: during the test, the sample to be tested is placed in a barrel, and the barrel is then placed in a heating furnace. The heating temperature is set, and after the sample is completely melted, a suitable rotor and speed are selected to test the viscosity of the wax liquid. After the viscosity data is stable, the melt viscosity of the sample is recorded; the melt viscosity of the wax emulsion is first dried into powder before testing.
[0055] Examples 1 to 24
[0056] Embodiments 1 to 24 respectively provide a digital transfer film coating and a digital transfer film. The components of the digital transfer film coating are shown in Table 1. The preparation method of the digital transfer film coating is as follows:
[0057] Add water, wax, thickener, adhesive, color fixing agent, filler and leveling agent into a stirring tank in turn and stir. After stirring evenly, filter and defoam to obtain a digital transfer film coating.
[0058] The preparation method of the digital transfer film is as follows:
[0059] The quantity transfer film coating was applied on the PET film by slit coating. During coating, the temperature was 120°C and the coating amount was 5g / m 2 After coating, the film was dried at 120°C for 1 min to obtain a digital transfer film.
[0060] Table 1
[0061]
[0062]
[0063]
[0064] Comparative Example 1
[0065] This comparative example provides a digital transfer film coating and a digital transfer film. The difference between this comparative example and Example 3 is that in this comparative example, the weight parts of polyethylene wax are 10 parts, the weight parts of montan wax emulsion are 10 parts, the weight parts of silicon dioxide are 14 parts, the weight parts of talc powder are 14 parts, and the weight parts of adhesive are 20 parts.
[0066] Comparative Example 2
[0067] This comparative example provides a digital transfer film coating and a digital transfer film. The difference between this comparative example and Example 2 is that this comparative example does not use montan wax emulsion, and the weight portion of polyethylene wax is 45 parts.
[0068] Comparative Example 3
[0069] This comparative example provides a digital transfer film coating and a digital transfer film. The difference between this comparative example and Example 2 is that the weight parts of polyethylene wax are 25 parts, the weight parts of montan wax emulsion are 50 parts, the weight parts of silicon dioxide are 4 parts, the weight parts of talcum powder are 4 parts, the weight parts of color fixing agent are 8 parts, and the weight parts of adhesive are 5 parts.
[0070] Comparative Example 4
[0071] This comparative example provides a digital transfer film coating and a digital transfer film. The difference between this comparative example and Example 2 is that this comparative example does not use silicon dioxide, and the weight proportion of talc is 18 parts.
[0072] Comparative Example 5
[0073] This comparative example provides a digital transfer film coating and a digital transfer film. The difference between this comparative example and Example 2 is that this comparative example does not use silicon dioxide, but uses an equal amount of fused alumina instead.
[0074] Effect Example 1
[0075] The digital transfer films prepared in the above examples and comparative examples were tested, and the test items included powder sticking, pattern peeling, printing appearance, and whether they can be peeled off hot or cold. The specific test methods are as follows:
[0076] (1) Powder sticking condition: 0.125m 2 A standard CMYK image was printed on a digital transfer film as a test product. The total area of the non-image area of the test product was tested. High molecular hot-melt adhesive powder was evenly sprinkled on the surface of the test product. The powder was shaken and the powder sticking condition was observed in the non-image area. The area of the powder sticking area was tested and the powder sticking ratio was calculated by the following formula: powder sticking ratio = powder sticking area area / total area of non-image area * 100%. If the powder sticking ratio is lower than 10%, it is within the normal range, indicating that the surface of the test product is dry and not easy to stick to the powder. If the powder sticking ratio is higher than 10%, it means that the powder sticking is excessive, indicating that the surface of the test product is sticky and not smooth.
[0077] (2) Pattern peeling: at 0.125m 2 Print a standard CMYK image on the digital transfer film, sprinkle powder and shake powder on the surface, peel it off after hot stamping, and measure whether there is a residual image on the surface of the intermediate medium after transfer. If there is a residual image, it cannot be peeled off, and if there is no residual image, it can be peeled off. If the temperature is 100-140℃, it can meet the requirements of hot peeling; if the peeling temperature is <80℃, it can meet the requirements of cold peeling; the force required for peeling is the peeling force, which is expressed by light, light+, medium, medium+, and heavy, respectively. 10-30g is light, 30-50g is light+, 50-100g is medium, 100-150g is medium+, and 200+g is heavy. The smaller the peeling force, the easier it is to peel.
[0078] (3) If the ink flows to the edge after printing, it means ink leakage; if the ink does not flow after printing, it means no ink leakage, that is, the ink fixing ability is good; after the image is dried, observe whether there are cracks and peeling on the image.
[0079] (4) Coating strength: Place the coated digital transfer film upward on the scrub resistance tester, brush it with a brush, and record the number of times the coating is brushed until it is damaged.
[0080] The test results are shown in Table 2.
[0081] Table 2
[0082]
[0083]
[0084] It can be seen from Table 2 that, compared with other embodiments, the coatings formed by the coatings of embodiments 2 to 4, embodiment 10, embodiment 12 and embodiments 17 to 19 have better coating strength, can be more smoothly cold and hot peeled, do not stick to powder, have good printing effects, and do not crack or ink flow after printing.
[0085] Compared with Example 2, the amount of wax added in Comparative Example 1 is too small, and the prepared digital transfer film cannot be thermally peeled; the amount of wax added in Comparative Example 3 is too much, and the wax is easy to migrate, resulting in easy cracking and powder sticking during printing, and the amount of filler and adhesive added at the same time is small, and the coating strength is also poor; Comparative Example 2 uses a single high-viscosity, high-melting-point polyethylene wax, and the resulting coating cannot be thermally peeled; Comparative Example 4 only uses a single filler, and the strength of the resulting coating is significantly deteriorated, with more powder sticking, and cracking after printing; Comparative Example 5 uses a single fused alumina, and the applied coating absorbs moisture severely, resulting in severe powder sticking to the coating, poor printing effect, and cracking.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A digital transfer film coating, characterized in that: The invention comprises the following components in parts by weight: 40 to 50 parts of wax, 1 to 2 parts of thickener, 15 to 24 parts of adhesive, 12 to 18 parts of color fixing agent, 1.5 to 2.5 parts of leveling agent, 0.5 to 1 part of disintegrant and 15 to 20 parts of filler; the wax comprises a first wax and a second wax, the melt viscosity of the first wax after drying is not higher than 80 mpa·s, and the melt viscosity of the second wax after drying is greater than 80 mpa·s; the melting point of the wax is 80 to 120°C; the first wax is montan wax emulsion; the second wax is polyethylene wax; the weight ratio of the first wax to the second wax is (0.5 to 2): 1; the disintegrant is selected from dry starch, sodium carboxymethyl starch, hydroxypropyl The filler comprises a first filler and a second filler, the weight ratio of the first filler to the second filler is (0.2-5):1, the first filler is selected from at least one of acrylic copolymers, silicon dioxide, calcium carbonate, kaolin, fumed alumina, zinc stearate, calcium stearate, talc, and titanium dioxide, and the particle size D90 of the first filler is less than 5 μm; the second filler is selected from at least one of acrylic copolymers, silicon dioxide, calcium carbonate, kaolin, fumed alumina, zinc stearate, calcium stearate, talc, and titanium dioxide, and the particle size D90 of the second filler is 5-15 μm.
2. The digital transfer film coating according to claim 1, characterized in that: The oil absorption value of the filler is not less than 30%.
3. A method for preparing a digital transfer film coating as claimed in any one of claims 1 to 2, characterized in that: The steps include: The wax, thickener, adhesive, color fixing agent, leveling agent, disintegrant and filler are mixed to obtain the digital transfer film coating.
4. Use of the digital transfer film coating according to any one of claims 1 to 2 in the preparation of a digital transfer film.
Citation Information
Patent Citations
Transfer printing film prepared by means of digital printing and preparation method and application thereof
CN106808820A
Water-based ink jet transfer printing method for textile personalized printing
CN109334292A
Production process of water-based digital ink-jet transfer printing intermediate medium
CN113022185A
Water-based heat transfer film coating as well as preparation method and application thereof
CN115785749A